Analysing Digital economy Strategy of Malawi against the Digital Economy Ecosystem Framework - Frank Makoza (ZBW - Leibniz Information Centre for Economics, 2022)
African countries are considering digital economy strategies to enhance their competitiveness, create economic value and improve the well-being of their citizens. This paper analysed the Malawi digital economy strategy (2021-2026) against the Digital Economy Ecosystem Framework. The findings showed consistency in elements for macro policy, digital foundations and digital adoption/Transformation; and core, services and solutions respectively. Nonetheless, some of the elements in the Malawi digital economy strategy were missing details and required attention. These include digital taxation, data sector, digital services laws and regulations and cyber security. Lack of details in these elements in the Malawi digital economy strategy can affect the planned activities and outcomes of the strategy. The study contributes towards an understanding of digital economy strategies in the context of developing countries.
Keywords: 330; Digital economy; Digital economy strategy; Digital Economy Kit; Digital technologies